Non-Hodgkin’s Lymphoma of the Uterine Cervix - Vasudev DS; Amrit Kaur Kaler (Online Journal of Health & Allied Sciences, 2012)
Non Hodgkin’s Lymphoma (NHL) causes many deaths worldwide and its incidence is increasing. They occur commonly in middle aged and elderly people and are disseminated at diagnosis. We present an interesting case of NHL in a 52 years old female, who presented with past a history of postmenopausal bleeding. A 3 x 5 cms endocervical polyp was noticed in the cervix. Biopsy of the polyp revealed it to be a CD20-positive diffuse large B-cell (DLBCL)-type NHL. She was diagnosed as stage IE after staging work-up. She attained a complete response, and has been in remission for 1 year 8 months.